Degreasing agent and fabric shaping process adopting degreasing agent
By using a degreasing agent containing non-ionic fluorocarbon surfactant, fatty alcohol polyoxyethylene ether and modified carbon nanotubes, the problem of unsatisfactory oil removal effect of the existing degreasing agent is solved, and the fabric is significantly improved Color fastness and color fixation rate.
Patent Information
- Application Number
- CN202311012236.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing oil degreasing agents are not effective in the oil removal process, resulting in a lower color fastness and color fixation rate of the fabric after dyeing.
An oil degreasing agent is used, which consists of a nonionic fluorocarbon surfactant, a fatty alcohol polyoxyethylene ether, a modified carbon nanotube, a diethylene glycol monobutyl ether and water, and is used by the combination of these components. The adsorption effect of forming small latex beams and modified carbon nanotubes can effectively remove oil in the fabric and improve the fixation effect of the dye.
The excellent color fastness and color fixation rate of the fabric are achieved, and the negative impact of oil residue on the dyeing effect is avoided.
Smart Images

Figure BDA0004390595650000051 
Figure BDA0004390595650000052 
Figure BDA0004390595650000061
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of dyeing and finishing, and in particular to a degreasing agent and a fabric shaping process using the degreasing agent. Background Art
[0002] In order to facilitate weaving and improve fiber strength, textile mills usually oil or sizing the yarn of the fabric to enhance the smoothness and strength of the fabric. Oiling the fabric is beneficial to weaving, but it increases the difficulty of dyeing and finishing. Generally, the oil must be removed before dyeing and finishing.
[0003] The general conventional degreasing process is to add a common degreasing agent at room temperature and heat it to 80-90℃ for washing. However, the common degreasing agents are not effective in degreasing fabrics. After conventional washing, more oil remains on the fabrics, resulting in low color fastness of the dyed fabrics, which cannot meet production requirements. If tetrachloroethylene with super strong washing ability is used for degreasing, the degreasing fabrics will feel hard because the degreasing is too clean, and the color fixation rate of the dyed fabrics is low. Summary of the invention
[0004] In order to overcome the unsatisfactory degreasing effect of existing degreasing agents, which causes the adverse effects of low color fastness or low color fixation rate of dyed fabrics, the present application provides a degreasing agent and a fabric shaping process using the degreasing agent.
[0005] In the first aspect, the present application provides a degreasing agent, which adopts the following technical solution: 1-5 parts of fluorocarbon surfactant; 2-4 parts of fatty alcohol polyoxyethylene ether; 2-4 parts of modified carbon nanotubes; 1-2 parts of sodium tripolyphosphate; 2-4 parts of diethylene glycol monobutyl ether; 15-25 parts water; The modified carbon nanotubes are prepared by treating carbon nanotubes with concentrated acid.
[0006] By adopting the above technical scheme, non-ionic fluorocarbon surfactant and fatty alcohol polyoxyethylene ether are used in combination to form smaller latex bundles, which enter the interior of the fabric during the degreasing process. The small latex bundles wrap the oil agent and dissolve it in water for removal. The modified carbon nanotubes enter the fabric to adsorb the oil agent, reducing the influence of the residual oil agent on the color fixation rate; further, the active groups on the surface of the modified carbon nanotubes and the porous structure of the carbon nanotubes have a good fixing effect on the dye, so that the fabric treated with the degreasing agent has excellent color fastness and color fixation rate.
[0007] Preferably, the length of the carbon nanotubes is 100-1000 nm.
[0008] By adopting the above technical solution, the length and diameter of the carbon nanotubes are optimized, so that the carbon nanotubes are smaller and have better dispersion properties, and are easier to enter the fabric, thereby improving the degreasing effect, so that the fabric treated with the degreasing agent has excellent color fastness and fixation rate.
[0009] Preferably, the fluorocarbon surfactant is a nonionic fluorocarbon surfactant.
[0010] By adopting the above technical scheme, the interaction between the ionic surfactant and the modified carbon nanotubes is relatively strong, which is not conducive to the adsorption of the emulsifier on the oil agent; the non-ionic fluorocarbon surfactant, fatty alcohol polyoxyethylene ether and the modified carbon nanotubes have a better compatibility effect, which improves the degreasing effect, so that the fabric treated with the degreasing agent has excellent color fastness and color fixation rate.
[0011] Preferably, the concentrated acid treatment process of the carbon nanotubes is as follows: The carbon nanotubes are added into concentrated acid formed by mixing concentrated nitric acid and concentrated sulfuric acid in a mass ratio of 1:(1-4), the mass ratio of the carbon nanotubes to the concentrated acid is 1:(10-14), ultrasonic treatment is performed for 40-60 minutes, and then the mixture is filtered, washed and dried to obtain the product.
[0012] By adopting the above technical scheme, after the carbon nanotubes are treated with concentrated nitric acid and concentrated sulfuric acid, the surface of the carbon nanotubes contains active groups, and more pits or holes are formed on the surface of the carbon nanotubes by corrosion, thereby increasing the specific surface area of the porous carbon nanotubes and improving the adsorption of oil stains and the fixation of dyes by the modified carbon nanotubes.
[0013] Preferably, the carbon nanotubes are subjected to a grafting treatment after being treated with concentrated acid, and the process of the grafting treatment is as follows: First, pyrrole, silver nitrate and modified carbon nanotubes are prepared in a weight ratio of 1:1:(5-7) for later use; Then, sodium dodecylbenzene sulfonate, xylene and deionized water were mixed in a weight ratio of (2-5) : 1 : 50, and stirred for 10 minutes at a stirring speed of 200 r / min to prepare a stirring liquid; Then the modified carbon nanotubes are added to the stirring liquid for ultrasonic dispersion, and then pyrrole and silver nitrate are added. After stirring at a stirring speed of 40-80 r / min for 24 hours, the mixture is filtered, washed and dried to prepare modified carbon nanotubes grafted with pyrrole.
[0014] By adopting the above technical scheme, pyrrole is grafted on the modified carbon nanotubes, and the surface of the oxidized porous carbon nanotubes is modified, thereby reducing the agglomeration of the porous carbon nanotubes themselves, improving the dispersibility, and increasing the interaction between the modified carbon nanotubes and the fabric fibers, thereby increasing the adhesion amount of the modified carbon nanotubes in the fabric.
[0015] Preferably, the degreasing agent further comprises 0.1-0.2 parts of polyvinyl alcohol.
[0016] By adopting the above technical scheme, polyvinyl alcohol is added to increase the viscosity of the degreasing agent, thereby improving the adhesion of the degreasing agent to the fabric, and synergizing with fluorocarbon surfactants and fatty alcohol polyoxyethylene to improve the degreasing efficiency; polyvinyl alcohol increases the adhesion amount of modified carbon nanotubes in the fabric, thereby making the fabric treated with the degreasing agent have excellent color fastness and color fixation rate.
[0017] In a second aspect, the present application provides a fabric shaping process using a degreasing agent.
[0018] A shaping process using the degreasing agent of the present application, comprising S1 degreasing treatment, S2 printing and dyeing and reduction cleaning and S3 shaping treatment; S1 degreasing treatment: the fabric is treated with water containing 1.2-3 g / L of degreasing agent at a temperature of 60-80°C for 20-40 min, with a bath ratio of 1:(10-15) to prepare a pretreated first preform; S2 printing, dyeing and reduction cleaning: dyeing and reduction cleaning the first fabric to prepare a second prefabricated product, and drying the second prefabricated product for standby use; S3 shaping treatment: the second preform after drying is treated with the first shaping agent, and then left to stand for 40-60 minutes; then treated with the second shaping agent, left to stand for 20-30 minutes, then washed, and then baked at 70-80°C for 20-30 minutes to prepare the shaped fabric; The mass ratio of the first setting agent to the second setting agent is 1:(1-3).
[0019] By adopting the above technical solution, the oil on the fabric is first treated with a deoiling agent so that the oil is effectively removed and adsorbed, and part of the modified carbon nanotubes remain in the fabric. During the dyeing process, the dye is combined and fixed with the modified carbon nanotubes, thereby improving the dye fixation rate and color fastness.
[0020] In the S3 setting treatment, by spraying the first setting agent and the second setting agent on the second preform, the substances in the film layer of the first setting agent and the second setting agent react to form a network structure, and a film layer is formed on the fabric and the fibers of the fabric, further improving the color fastness of the fabric; the film layer formed on the fabric fibers reduces the interaction between the active groups on the fabric fibers, so that the fabric has excellent stability and color fastness.
[0021] Preferably, the first setting agent is a mixture of 1-2 parts of sodium polyacrylate, 1-2 parts of anionic silicone oil, 0.5-1.5 parts of fatty alcohol polyoxyethylene ether and 30-50 parts of deionized water; The second setting agent is prepared by mixing 1-2 parts of a penetrant, 3-5 parts of hydroxyl-terminated dimethyl silicone oil, 0.5-0.7 parts of an aziridine crosslinking agent, 0.2-0.6 parts of a dispersant and 30-50 parts of deionized water.
[0022] By adopting the above technical solution, hydroxyl-terminated dimethyl silicone oil and aziridine cross-linking agent form a network structure on the fabric, thereby improving the color fastness of the fabric.
[0023] Sodium polyacrylate has good binding force with modified carbon nanotubes or ammonium ions of modified carbon nanotubes, thereby improving the binding force between the network structure and the fabric, and further improving the stability and color fastness of the fabric.
[0024] Preferably, in the S3 setting treatment, the second preform is steam set before being treated with the first setting agent, and the steam setting temperature is 110° C. and the time is 30 minutes.
[0025] By adopting the above technical solution, the fabric is steam-set before being treated with the first setting agent, which further improves the bonding strength between the network structure and the fabric, and further improves the color fastness and stability of the fabric.
[0026] Preferably, the penetrant is fatty alcohol polyoxyethylene ether or Tween-20, and the dispersant is dodecyl dimethyl betaine or tert-octylphenol.
[0027] By adopting the above technical scheme, the penetrant is selected as fatty alcohol polyoxyethylene ether or Tween-20, and the dispersant is dodecyl dimethyl betaine or tert-octylphenol, so that the second setting agent is better in contact with the first setting agent, so that the first setting agent and the second setting agent are fully reacted, and further, the density of the formed network structure is increased, thereby improving the friction resistance, color fastness and stability of the fabric.
[0028] In summary, this application has the following beneficial effects: 1. The degreasing agent includes fluorocarbon surfactant, fatty alcohol polyoxyethylene ether, modified carbon nanotubes, diethylene glycol monobutyl ether and water. Through the use of non-ionic fluorocarbon surfactant and fatty alcohol polyoxyethylene ether, the degreasing agent forms small micelles with low surface energy, enters the fabric to wrap and remove the oil, and the modified carbon nanotubes enter the fabric to adsorb the residual oil, reducing the effect of the residual oil on the color fixation rate; further, the active groups on the surface of the modified carbon nanotubes and the porous structure of the carbon nanotubes have a good fixing effect on the dye, so that the fabric treated with the degreasing agent has excellent color fastness and color fixation rate.
[0029] 2. The high temperature during the degreasing, dyeing and setting processes causes the fabric to shrink. The combination of the first setting agent and the second setting agent forms a network structure on the fiber surface of the fabric, further improving the stability and color fastness to friction of the fabric.
[0030] 3. The sodium polyacrylate and / or anionic silicone oil added to the first setting agent interacts with the modified carbon nanotubes in the fabric, thereby enhancing the interaction between the film layer formed by the first setting agent and the second setting agent and the fabric, further enhancing the stability and color fastness to friction of the fabric. DETAILED DESCRIPTION
[0031] raw material Polyvinyl alcohol (viscosity 43-45mPa·s), sodium polyacrylate (average molecular weight: 5000), hydroxyl-terminated dimethyl silicone oil (hydroxyl content: 8), bentonite (average particle size of about 5μm), sodium carboxymethyl cellulose (degree of substitution ≥9.0).
[0032] Preparation example of intermediate Preparation Example 1, a modified carbon nanotube, using raw materials as shown in Table 1, the preparation process is as follows: Carbon nanotubes with a length of 100 nm and a diameter of 20 nm were added to a mixture of 68% concentrated nitric acid and 93% concentrated sulfuric acid in a mass ratio of 1:1 to form concentrated acid, and the mass ratio of carbon nanotubes to concentrated acid was 1:10. After ultrasonic treatment for 60 minutes, the mixture was filtered, rinsed with deionized water until the eluent was neutral, and dried at 50°C for 2 hours.
[0033] First, pyrrole, silver nitrate and carbon nanotubes treated with concentrated acid are taken in a weight ratio of 1:1:5 for use; then sodium dodecylbenzene sulfonate, xylene and deionized water are taken in a weight ratio of 2:1:50, mixed, and stirred for 10 minutes at a stirring speed of 200 r / min to prepare a stirring liquid.
[0034] The modified carbon nanotubes were then added to the stirring liquid for ultrasonic dispersion, and then pyrrole and silver nitrate were added. After stirring at a stirring speed of 80 r / min for 24 hours, the filtered mixture was washed three times with N-methylpyrrolidone, acetone and deionized water respectively. After washing, the modified carbon nanotubes were placed in a vacuum oven at 60°C and dried for 24 hours to obtain the modified carbon nanotubes.
[0035] Preparation Example 2-3, a modified carbon nanotube, is different from Preparation Example 1 in that the types and weights of carbon nanotubes and mixed acids used, and the preparation process of the modified carbon nanotubes are different, as shown in Table 1.
[0036] Table 1 Types and weights of raw materials and preparation processes for modified carbon nanotubes in Preparation Examples 1-3 The concentrated acid in Preparation Example 2 is a mixed acid of 68% concentrated nitric acid and 93% concentrated sulfuric acid in a mass ratio of 1:4; the concentrated acid in Preparation Example 3 is a mixed acid of 68% concentrated nitric acid and 93% concentrated sulfuric acid in a mass ratio of 1:3.
[0037] Preparation Example 4, a modified carbon nanotube, is different from Preparation Example 1 in that 93% concentrated sulfuric acid is used in an equal amount to replace 68% concentrated nitric acid.
[0038] Preparation Example 5, a modified carbon nanotube, is different from Preparation Example 1 in that a carbon nanotube with a length of 2000 nm and a diameter of 30 nm is used.
[0039] Preparation Example 6, a modified carbon nanotube, is different from Preparation Example 1 in that, after being treated with concentrated acid, the carbon nanotube is not treated with a stirring liquid consisting of pyrrole, silver nitrate, sodium dodecylbenzene sulfonate, xylene and deionized water. Example
[0040] Example 1, a degreasing agent, using raw materials as shown in Table 2, the preparation process is as follows: Fluorocarbon surfactant, fatty alcohol polyoxyethylene ether, modified carbon nanotubes, sodium tripolyphosphate, diethylene glycol monobutyl ether, polyvinyl alcohol and water were mixed and stirred at 600 r / min for 20 minutes to prepare a degreasing agent.
[0041] Example 2-3, a degreasing agent, is different from Example 1 in that the types and weight settings of raw materials are different, as shown in Table 2.
[0042] Table 2 Types and weight settings of raw materials for degreasing agents in Example 2-3 Example 4, a degreasing agent, differs from Example 1 in that anionic fluorocarbon surfactant F-8907 is replaced by nonionic fluorocarbon surfactant FC327 in equal amounts.
[0043] Example 5-7, a degreasing agent, is different from Example 1 in that the modified carbon nanotubes of Preparation Examples 4-6 are used in sequence.
[0044] Embodiment 8 is a degreasing agent, which is different from Embodiment 7 in that polyvinyl alcohol is not used.
[0045] Example 9, a fabric shaping process using a degreasing agent, using raw materials as shown in Table 3-4, and the preparation process is as follows: S1 degreasing treatment: using a high temperature and high pressure overflow dyeing machine, the polyester fabric is treated with water containing 1.2 / L of degreasing agent at a temperature of 80°C for 20 minutes, with a bath ratio of 1:10, and after the degreasing treatment, it is washed and dried to prepare a pretreated first preform; S2 printing and dyeing and reduction cleaning: Dyeing treatment: a plain fabric woven from polyester / cotton blended fibers with a mass ratio of 1:1 is dyed with dyeing liquid using a high temperature and high pressure overflow dyeing machine, and the bath ratio is 1:10.
[0046] The dyeing solution includes Disperse Red 50 2.25% (owf), Leveling Agent RX-820 1.0 g / L, and Acetic Acid 1.2 g / L.
[0047] Put the dyeing liquid into the dye kettle; wind the first preform flatly on the dyeing shaft and put it into the dyeing kettle; adjust the system pressure to 0.35±0.5Mpa; circulate the fluid dissolved with disperse dye between the inner and outer layers of the curled polyester fiber fabric through a circulating pump, raise the temperature to 125±5°C at a rate of 1.5°C / min, and circulate dyeing for 1 hour; after completing the circulated dyeing, reduce the system pressure and temperature.
[0048] Reduction cleaning: The dyed polyester fiber fabric is subjected to reduction cleaning for 15 minutes using a cleaning agent of 1.2% (owf) sodium hydroxide and 3g / L hydrosulfite, and then dehydrated and transported to a width-opening machine for width-opening to prepare a second preform.
[0049] S3 shaping treatment: steam-shape the second preform at 110°C for 30 minutes, spray the first shaping agent on the surface of the second preform after steam shaping, and then let it stand for 40 minutes; then spray the second shaping agent, let it stand for 20 minutes, then rinse with water and bake at 80°C for 20 minutes to prepare the shaped fabric.
[0050] The first setting agent is a mixture of sodium polyacrylate, anionic silicone oil, fatty alcohol polyoxyethylene ether and deionized water.
[0051] The second setting agent is prepared by mixing a penetrant, hydroxyl-terminated dimethyl silicone oil, an aziridine cross-linking agent, a dispersant and deionized water.
[0052] Embodiments 10-11, a fabric shaping process using a degreasing agent, differ from Embodiment 9 in that the weight of the degreasing agent and the degreasing process settings in the S1 degreasing treatment are different, and in the S3 shaping treatment, the types and weights of the raw materials of the first shaping agent and the second shaping agent are different, and the shaping process parameters are set differently, as shown in Table 3-4.
[0053] Table 3 is a list of the weight of the degreasing agent and the degreasing process parameter settings in the S1 degreasing treatment in Examples 9-11.
[0054] Table 4 is a list of raw material types and weights of the first setting agent and the second setting agent in the S3 setting treatment in Examples 9-11, and setting process parameter settings.
[0055] Example 12, a fabric shaping process using a degreasing agent, differs from Example 9 in that an equal amount of sodium carboxymethyl cellulose is used to replace sodium polyacrylate, and an equal amount of hydroxy-terminated dimethyl silicone oil is used to replace anionic silicone oil.
[0056] Embodiment 13, a fabric shaping process using a degreasing agent, differs from Embodiment 9 in that steam shaping is not used in the S3 shaping treatment.
[0057] Example 14, a fabric setting process using a degreasing agent, differs from Example 9 in that sodium dodecyl sulfonate is used in an equal amount to replace fatty alcohol polyoxyethylene AEO3; hexadecyltrimethylammonium bromide is used in an equal amount to replace dodecyl dimethyl betaine; and the first setting agent and the second setting agent are sprayed first, and then steam setting is performed.
[0058] Example 15, a fabric shaping process using a degreasing agent, differs from Example 9 in that an equal amount of polyethanol 2000 is used to replace the hydroxy-terminated dimethyl silicone oil.
[0059] Embodiments 16-20, a fabric shaping process using a degreasing agent, differ from Embodiment 9 in that Embodiments 4-8 are used in sequence.
[0060] Comparative Example Comparative Example 1, a degreasing agent, differs from Example 20 in that an equal amount of a fluorocarbon surfactant is used to replace the modified carbon nanotubes.
[0061] Comparative Example 2, a degreasing agent, differs from Example 20 in that bentonite is used in an equal amount to replace the modified carbon nanotubes, and fatty alcohol polyoxyethylene ether is used in an equal amount to replace the fluorocarbon surfactant.
[0062] Comparative Example 3, a degreasing agent, differs from Example 20 in that fatty alcohol polyoxyethylene ether is used in equal amounts to replace the modified carbon nanotubes and the fluorocarbon surfactant.
[0063] Comparative Example 4 is a degreasing agent, which differs from Example 20 in that 6 kg of carbon nanotubes are used to replace 2 kg of modified carbon nanotubes in Example 8, and an equal amount of sodium hydroxide is used to replace sodium tripolyphosphate.
[0064] Comparative Examples 5-8, a fabric shaping process using a degreasing agent, differs from Example 20 in that the degreasing agents of Comparative Examples 1-4 are used in sequence.
[0065] Comparative Example 9 is a fabric setting process using a degreasing agent, which differs from Example 20 in that the first setting agent is not used in the S3 setting treatment.
[0066] Comparative Example 10 is a fabric shaping process using a degreasing agent, which differs from Example 20 in that S1 degreasing treatment is not used.
[0067] Performance testing Test 1: Color fastness to washing test Test method: The test samples were evaluated for color fastness to washing in accordance with GB / T 12490-2014 "Textiles - Tests for color fastness - Color fastness to domestic and commercial washing". The test samples were rated according to the gray scale, and the average value of N = 3 for each test sample was taken as the color fastness to washing result.
[0068] Washing process: Place the same test sample in a washing machine (Haier EB80MO09 8KG), set the water volume to 18L, add detergent (Diao brand sterilization phosphorus-free detergent), 3g of detergent per liter of water, set the washing temperature to 50℃, the washing time to 30min, and the number of washes to 10 times.
[0069] Test 2: Color fastness to rubbing test method: According to the test method in GB / T 3920-2008 "Textiles - Tests for Color Fastness - Color Fastness to Rubbing", the abrasion color fastness test was carried out in a rubbing color fastness tester, and then the gray sample card was used for rating, and the values were recorded and the average value (the average value of the sample N=3 tests was taken) was taken as the color fastness to rubbing result.
[0070] Test samples: In Test 1 and Test 2, the fabrics prepared by the fabric shaping process using a degreasing agent in Examples 9-20 were used as test samples; the fabrics prepared by the fabric shaping process using a degreasing agent in Comparative Examples 5-10 were used as comparative samples.
[0071] Test 3: Fixation rate detection method: After dyeing, collect the dyeing residual liquid, collect the soaping residual liquid after reduction cleaning, wash the sample with clean water, collect the washing liquid, combine the washing liquid, soaping residual liquid and dyeing residual liquid, collectively referred to as the dye bath, and dilute to a certain concentration. The absorbance of the dye bath of the test sample and the comparison sample is tested as A1 (sample N=3 tests take the average value), and calculate the volume V1 of the diluted dye bath.
[0072] Test samples: Dye bath in fabric setting process using degreasing agent in Examples 9-20; Comparative samples: Comparative Examples 5-11 use a dye bath in the fabric shaping process using a degreasing agent; Blank sample: The difference between the blank experiment and the setting with degreasing agent in Example 9 is that S1 degreasing treatment is not used; no fabric is added in S2 printing and dyeing and reduction cleaning. The residual liquid after the soaping residual liquid and the dyeing residual liquid in the blank experiment are combined as blank samples.
[0073] Dilute the soaping residue and dyeing residue in the blank test to a certain concentration, measure the absorbance A2 (sample N=3 tests and take the average value), and calculate the volume V2 after dilution.
[0074] Calculation of the fixation rate F of each sample: fixation rate F = 100% - XX = (A1V1 / A2V2) * 100% Where: X-the percentage of dye in the dyeing residual solution to the total dye amount.
[0075] Test 4: Shrinkage The following shrinkage formula is used to calculate the radial shrinkage of the fabric.
[0076] Shrinkage rate = (L0-L1) / L0×100% Wherein: L0 is the warp length before washing; L1 is the warp length after washing, cm.
[0077] Washing process: Place the same test sample in a washing machine (Haier EB80MO09 8KG), set the water volume to 18L, add detergent (Diao brand sterilization phosphorus-free detergent), 3g of detergent per liter of water, set the washing temperature to 60℃, the washing time to 40min, and the number of washes to 10 times.
[0078] Experimental results: The experimental results of color fastness to washing, color fastness to rubbing, color fixation rate and shrinkage rate of cotton-polyester fabrics prepared by the fabric shaping process using a degreasing agent in Examples 9-20 of Test 3 and Test 4 and Comparative Examples 5-10 are shown in Table 5.
[0079] Table 5 Results of color fastness to washing, color fastness to rubbing, color fixation rate and shrinkage rate of cotton-polyester fabrics prepared by using Examples 9-20 and Comparative Examples 5-10 Combining Examples 9-20 and Comparative Examples 5-10 and Table 5, it can be seen that: The cotton-polyester fabric prepared by the fabric shaping process using a degreasing agent in Examples 9-20 has better color fastness to washing, color fastness to rubbing, color fixation rate and shrinkage rate than those in Comparative Documents 5-10, because in Examples 9-20, a fluorocarbon surfactant, a fatty alcohol polyoxyethylene ether, a modified carbon nanotube and diethylene glycol monobutyl ether are used in combination in the degreasing agent, and the fluorocarbon surfactant is used in combination with the fatty alcohol polyoxyethylene ether, so that the degreasing agent forms smaller latex particles, which are more effectively combined with the oil agent in the fabric. At the same time, the modified carbon nanoparticles in the fabric adsorb the oil agent, and the smaller latex particles are used to remove oil and the modified carbon nanotubes are used in combination to adsorb the oil agent, so that the degreasing agent has a better degreasing effect; after degreasing, part of the modified carbon nanotubes remain in the fabric, and the active groups on the surface of the modified carbon nanotubes and the porous structure of the carbon nanotubes make the modified carbon nanotubes have a better fixing effect on the dye, so that the fabric treated with the degreasing agent has excellent color fastness to washing, color fastness to rubbing and color fixation rate.
[0080] The color fastness to washing, color fastness to rubbing, color fixation rate and shrinkage rate of the cotton and polyester fabrics prepared by the fabric shaping process using a degreasing agent in Examples 9-20 are better than those in Comparative Example 8. This may be because sodium tripolyphosphate has a dispersion-promoting effect on the modified carbon nanotubes, and the amount of modified carbon nanotubes used is too much, which is easy to agglomerate, which is not conducive to the modified carbon nanotubes entering the interior of the fabric, resulting in a small content of modified carbon nanotubes in the fabric, resulting in lower color fastness to washing, color fastness to rubbing, and color fixation rate of the prepared cotton and polyester fabrics, and a higher shrinkage rate.
[0081] The color fastness to washing, color fastness to rubbing, color fixation rate and shrinkage rate of the cotton-polyester fabric prepared by Examples 9-11 are better than those of Example 12. This may be because there are active groups or ammonium ions on the surface of the modified carbon nanotubes, and the sodium polyacrylate and anionic silicone oil are used in combination with the modified carbon nanotubes to have good binding force, which improves the binding force between the film layer formed by the first setting agent and the second setting agent and the cotton-polyester fabric fiber and the density of the film layer, reduces the interaction of active groups on the fabric fibers and the migration of dyes in the fabric, so that the fabric treated with the degreasing agent has excellent color fastness to washing, color fastness to rubbing and color fixation rate.
[0082] The possible reason is that sodium carboxymethyl cellulose has a network structure and the effect of hydroxyl-terminated dimethyl silicone oil on modified carbon nanotubes is weaker than that of anionic silicone oil, resulting in lower color fastness to washing, color fastness to rubbing, and color fixation rate of the cotton-polyester fabric prepared by Example 12, and higher shrinkage rate.
[0083] The color fastness to washing, color fastness to rubbing, color fixation rate and shrinkage rate of the cotton-polyester fabric prepared by Examples 9-11 are better than those of Example 13. This may be because after the cotton-polyester fabric is steam-set, the fibers of the cotton-polyester fabric are relaxed, which is more conducive to the combination of the raw materials in the first setting agent and the second setting agent with the modified carbon nanotubes in the cotton-polyester fabric, so that more components of the first setting agent and the second setting agent are fixed by the cotton-polyester fabric fibers, thereby improving the binding force and density of the film layer formed by the reaction of the first setting agent and the second setting agent with the fabric fibers, and reducing the interaction of active groups on the fabric fibers and the migration of dyes in the fabric.
[0084] The color fastness to washing, color fastness to rubbing, color fixation rate and shrinkage rate of the cotton-polyester fabric prepared by Examples 9-11 are better than those of Example 14. This may be because the sodium dodecyl sulfate and hexadecyltrimethylammonium bromide used in Example 14 interfere with the anions in the first setting agent, the second setting agent stays on the surface of the first setting agent, the formed film layer has less crosslinking and lower strength, and no steam setting is performed after spraying the first setting agent, resulting in weak bonding between the formed film layer and the fabric fibers, resulting in lower color fastness to washing, color fastness to rubbing, and color fixation rate of the prepared cotton-polyester fabric, and higher shrinkage rate.
[0085] The color fastness to washing, color fastness to rubbing, color fixation rate and shrinkage rate of the cotton-polyester fabric prepared by Examples 9-11 are better than those of Example 15. This may be because Example 15 uses polyethanol 2000 to replace hydroxy-terminated dimethyl silicone oil, which reduces the friction resistance of the film layer formed by the reaction of the first fixing agent and the second fixing agent, and its compatibility with the first fixing agent is worse than that of hydroxy-terminated dimethyl silicone oil. The second fixing agent stays on the surface of the first fixing agent, and the formed film layer has less crosslinking and lower strength, resulting in lower color fastness to washing, color fastness to rubbing, and color fixation rate of the prepared cotton-polyester fabric, and higher shrinkage rate.
[0086] The color fastness to washing, color fastness to rubbing, color fixation rate and shrinkage rate of the cotton-polyester fabric prepared by Examples 9-11 are better than those in Example 16. This may be because the anionic fluorocarbon surfactant has a good binding force with the modified carbon nanotubes. In Example 16, after the non-ionic fluorocarbon surfactant FC327 is used to replace the anionic fluorocarbon surfactant F-8907 in an equal amount, the binding force between the film layer formed by the reaction of the first setting agent and the second setting agent and the fabric and the fabric fiber becomes poor, resulting in the prepared cotton-polyester fabric having lower color fastness to washing, color fastness to rubbing, and color fixation rate, and higher shrinkage rate.
[0087] The color fastness to washing, color fastness to rubbing, color fixation rate and shrinkage rate of the cotton-polyester fabric prepared by Examples 9-11 are better than those of Example 17. This may be because the carbon nanotubes are treated with concentrated acid of 93% concentrated sulfuric acid, which corrodes the surface of the carbon nanotubes too strongly, causing the surface network structure of the carbon nanotubes to collapse, resulting in a decrease in the adsorption capacity of the modified carbon nanotubes and a weakening of the interaction between the film layers formed by the reaction with the first setting agent and the second setting agent.
[0088] The color fastness to washing, color fastness to rubbing, color fixation rate and shrinkage rate of the cotton-polyester fabric prepared by Examples 9-18 are better than those of Examples 19-20. This may be because the carbon nanotubes treated with concentrated acid have improved dispersibility of the modified carbon nanotubes after pyrrole grafting and increased the amount of modified carbon nanotubes attached to the cotton-polyester fabric, and the surface of the modified carbon nanotubes grafted with pyrrole has ammonium ions, which have better binding force with the anions in the first setting agent, thereby enhancing the binding force between the film layer and the fabric fiber.
[0089] The addition of polyvinyl alcohol in the degreasing agent works synergistically with the pyrrole side chains on the modified carbon nanotubes to improve the dispersibility of the modified carbon nanotubes and increase the amount of modified carbon nanotubes attached to the cotton and polyester fabrics, so that the fabrics treated with the degreasing agent have excellent color fastness to washing, color fastness to rubbing and color fixation rate.
[0090] The specific embodiments in this application are merely explanations of this application and are not limitations of this application. After reading this specification, those skilled in the art may make modifications to this embodiment without any creative contribution as needed, but as long as they are within the scope of the claims of this application, they are protected by the patent law.
Claims
1. A degreasing agent, characterized in that: In parts by mass, it includes the following raw materials: 1-5 parts of fluorocarbon surfactant; 2-4 parts of fatty alcohol polyoxyethylene ether; 2-4 parts of modified carbon nanotubes; 1-2 parts of sodium tripolyphosphate; 2-4 parts of diethylene glycol monobutyl ether; 15-25 parts water; The modified carbon nanotubes are prepared by treating carbon nanotubes with concentrated acid.
2. The degreasing agent according to claim 1, characterized in that The length of the carbon nanotube is selected to be 100-1000nm, and the tube diameter is 5-20nm.
3. The degreasing agent according to claim 1, characterized in that The fluorocarbon surfactant is a nonionic fluorocarbon surfactant.
4. The degreasing agent according to claim 1, characterized in that The preparation process of the modified carbon nanotubes is as follows: The carbon nanotubes are added into concentrated acid formed by mixing concentrated nitric acid and concentrated sulfuric acid in a mass ratio of 1: (1-4), wherein the mass ratio of the carbon nanotubes to the concentrated acid is 1: (10-14), and ultrasonic treatment is performed for 40-60 minutes, followed by filtering, washing and drying to obtain the product.
5. The degreasing agent according to claim 1, characterized in that The carbon nanotubes are subjected to a grafting treatment after being treated with concentrated acid, and the process of the grafting treatment is as follows: First, pyrrole, silver nitrate and modified carbon nanotubes are prepared in a weight ratio of 1:1:(5-7) for later use; Then, sodium dodecylbenzene sulfonate, xylene and deionized water were mixed in a weight ratio of (2-5) : 1 : 50, and stirred for 10 minutes at a stirring speed of 200 r / min to prepare a stirring liquid; Then the modified carbon nanotubes are added to the stirring liquid for ultrasonic dispersion, and then pyrrole and silver nitrate are added. After stirring at a stirring speed of 40-80 r / min for 24 hours, the mixture is filtered, washed and dried to prepare modified carbon nanotubes grafted with pyrrole.
6. The degreasing agent according to claim 1, characterized in that The degreasing agent also includes 0.1-0.2 parts of polyvinyl alcohol.
7. A fabric shaping process using the degreasing agent according to any one of claims 1 to 6, characterized in that: Including S1 degreasing treatment, S2 printing and dyeing and reduction cleaning and S3 setting treatment; S1 degreasing treatment: the fabric is treated with water containing 1.2-3 g / L of degreasing agent at a temperature of 60-80°C for 20-40 minutes, with a bath ratio of 1: (10-15), to prepare a pre-treated first preform; S2 printing, dyeing and reduction cleaning: dyeing and reduction cleaning the first fabric to prepare a second prefabricated product, and drying the second prefabricated product for standby use; S3 shaping treatment: the second preform after drying is treated with the first shaping agent, and then left to stand for 40-60 minutes; then treated with the second shaping agent, left to stand for 20-30 minutes, then washed, and then baked at 70-80°C for 20-30 minutes to prepare the shaped fabric; The mass ratio of the first setting agent to the second setting agent is 1:(1-3).
8. A fabric shaping process using a degreasing agent according to claim 7, characterized in that: The first setting agent is prepared by mixing 1-2 parts of sodium polyacrylate, 1-2 parts of anionic silicone oil, 0.5-1.5 parts of fatty alcohol polyoxyethylene ether and 30-50 parts of deionized water; The second setting agent is prepared by mixing 1-2 parts of a penetrant, 3-5 parts of hydroxyl-terminated dimethyl silicone oil, 0.5-0.7 parts of an aziridine crosslinking agent, 0.2-0.6 parts of a dispersant and 30-50 parts of deionized water.
9. A fabric shaping process using a degreasing agent according to claim 8, characterized in that: In the S3 setting treatment, the second preform is steam set before being treated with the first setting agent, and the steam setting temperature is 110° C. and the time is 30 minutes.
10. A fabric shaping process using a degreasing agent according to claim 8, characterized in that: The penetrant is fatty alcohol polyoxyethylene ether or Tween-20, and the dispersant is dodecyl dimethyl betaine or p-tert-octylphenol.